The dilemma of Mexico's development : the roles of the private and public sectors - Vernon, Raymond (Cambridge, Mass. : Harvard University Press, 1963)
This a study of the relative roles of private enterprise and government in Mexico. It covers topics like: Mexico today (1963); Juarez and Diaz; the revolution and after 1910-1940; economic policies and performance since 1940; the politicos and tecnicos since 1940; leadership ideology in the private sector since 1940; and the Mexican dilemma.
Bibliographical references included in "Notes" (p. [201]-218)
lje 19/10/18
Loans
Keywords: Economic development; Economic growth; Economy-Mexico; Mexico